Relative permeability of homogenous‐wet and mixed‐wet porous media as determined by pore‐scale lattice Boltzmann modeling. Issue 5 (6th May 2014) - Landry, C. J.; Karpyn, Z. T.; Ayala, O.
Abstract We present a pore‐scale study of two‐phase relative permeability in homogenous‐wet porous media, and porous media altered to a mixed‐wet state. A Shan‐Chen type multicomponent lattice Boltzmann (LB) model is employed to determine pore‐scale fluid distributions and relative permeability. Mixed‐wet states are created by altering the wettability of solid surfaces in contact with the nonwetting phase at the end of steady state simulation of initially homogenous‐wet porous media. To ensure accurate representation of fluid‐solid interfacial areas, we compare LB simulation results to experimental measurements of interfacial fluid‐fluid and fluid‐solid areas determined by X‐ray computed microtomography imaging of water and oil distributions in bead packs. The LB simulations are found to match experimental trends observed for fluid‐fluid and fluid‐solid interfacial area‐saturation relationships. The relative permeability of both fluids in the homogenous‐wet porous media was found to decrease with a decreasing contact angle. The relative permeability of both fluids in the altered, mixed‐wet porous media was found to decrease for all mixed‐wet states in comparison to the initial homogenous‐wet states. The nonwetting phase relative permeability decreased significantly, while the wetting phase experienced only a minor decrease. The significance of the decrease was found to be dependent on the distribution of the unaltered solid surfaces, with less dependence on the severity of alteration.